PENERAPAN MODEL LITERATURE CIRCLE DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 4 BANDA ACEH - Nurlaili Manik; Intan Safiah; Hasniyati (STKIP Subang, 2026)
Critical thinking skills are one of the essential competencies that need to be developed in elementary school students. However, students’ critical thinking skills in Indonesian language learning are still relatively low because learning activities tend to be teacher-centered and provide limited opportunities for students to actively discuss and express their ideas. Therefore, an appropriate learning model is needed to facilitate students’ active participation in the learning process. This study aimed to describe the implementation of the Literature Circle model in developing the critical thinking skills of fifth-grade students in Indonesian language learning on fictional story materials at SD Negeri 4 Banda Aceh. This research employed a qualitative descriptive approach involving 20 fifth-grade students as research subjects. Data were collected through observation and essay tests. Observation was used to examine students’ learning activities and critical thinking skills during the learning process, while the essay test was administered to measure students’ critical thinking skills after the implementation of the Literature Circle model. The results revealed that students’ learning activities were categorized as very good with an average score of 4.00. Students’ critical thinking skills based on observation obtained an average score of 3.33 and were categorized as good. Furthermore, the test results showed an average score of 84.25, which was categorized as high, with 100% classical mastery learning. These findings indicate that the Literature Circle model contributes positively to the development of students’ critical thinking skills in Indonesian language learning.